Lean Production, Izzat and Industrial Conflict in the Indian Auto Sector: A Case Study - Mathew, Sagi; Burgess, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
SummaryThe purpose of this article is to highlight the role that Izzat played in the unfolding industrial disputation that emerged at the Toyota plant in Bangalore between 1999 and 2007. Isolated instances contributed to a build-up of employee and community resentment at what was perceived as an attack on Izzat. Behind the events is the attempt to transpose Japanese “lean production and management systems” into an Indian subsidiary where local industrial and cultural conditions were not suitable for the imposition of such practices from headquarters to a subsidiary.The result of the analysis contributes to the understanding of workplace industrial relations (IR) in India and the centrality of Izzat. Within India, the significance of trade unions; the respect of employees; the importance of family and community; the importance of seniority; and the role of respect and honour are factors that multinationals often fail to understand in the design and implementation of their production and HRM systems.The study contributes to the debate over the transferability of standardized HRM policies and practices. MNEs should play a proactive role in supporting the employees of subsidiaries to adjust to and accommodate new paradigms in workplace industrial relations. The aggressive production and HRM practices at the Toyota plant were not compatible with the norms and cultural institutions of the Indian workforce. One of the key implications of this research is that foreign production, organizational and industrial relations systems and practices cannot be transplanted into host-country environments without the due recognition of key cultural conditions, notably Izzat in India.